2020
DOI: 10.1111/1759-7714.13668
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional control and toxicity after pleurectomy/decortication and intensity‐modulated pleural radiation therapy in patients with malignant pleural mesothelioma

Abstract: Background: Treatment of malignant pleural mesothelioma (MPM) represents a major challenge for oncologists. Multimodality treatment, which generally involves induction chemotherapy, surgery and radiotherapy have recently shown promising results. The aim of this study was to evaluate the locoregional control and toxicity of intensity modulated radiotherapy (IMRT) after pleurectomy and decortication (P/D) as part of trimodality therapy for patients with locally advanced MPM. Methods: We prospectively analyzed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Another approach to improve local control to be further investigated is adding intensity-modulated radiotherapy to the pleura, which has been shown to be feasible in two phase 2 trials [ 23 , 24 ] and is currently being investigated in a phase 3 trial [ 25 ]. During surgery, applying hyperthermic intrathoracic chemotherapy may also improve local control, but this modality has not yet been evaluated in a randomised trial, and its early results should be confirmed in controlled studies [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to improve local control to be further investigated is adding intensity-modulated radiotherapy to the pleura, which has been shown to be feasible in two phase 2 trials [ 23 , 24 ] and is currently being investigated in a phase 3 trial [ 25 ]. During surgery, applying hyperthermic intrathoracic chemotherapy may also improve local control, but this modality has not yet been evaluated in a randomised trial, and its early results should be confirmed in controlled studies [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intensity modulated pleural radiation therapy has been shown to be safe with an acceptable rate of radiation pneumonitis; together with chemotherapy and PD in has been advocated as a new lung-sparing treatment paradigm for patients with locally advanced MPM, yielding acceptable locoregional control (21,22).…”
Section: Review Articlementioning
confidence: 99%